G595 Are paediatric specialist trainees prepared to manage transition, what are the knowledge gaps and how can training be improved. (May 2019) - Alam, S; Thomas, S; Farr, E; van der Voort, J
Abstract : Background: Local audit demonstrates 62% missed outpatient opportunities to initiate transition tools and 81% of letters fail to mention transition, possibly reflecting inadequate training. This study aims to investigate the training needs of paediatric trainees preparing to manage transition by identifying knowledge gaps and ways in which training can be improved. Methods: Paediatric trainees of mixed seniority (ST1–8) were invited to complete a questionnaire. Open-questions explored what should be included in outpatient consultations to facilitate transition, and how training could be improved. A forum led by an expert-patient was then held, and a second part of the questionnaire completed. Data was thematically analysed until saturation. Results: 25 participants completed questionnaires (average grade ST4). Only 24% had knowledge of transition tools. The more senior the trainee, the more confident they felt to manage transition (average=2.4/5) and the earlier suggested age of transition initiation. The suggested average age that transition should be initiated was 13.25 years. 8 themes capture what should be incorporated into consultations to facilitate transition (most frequent first): social impact, independence, support networks, future plans, psychological impact, liaison with adult services, disease understanding and risky activities. 8 themes capture recommendations to improve training (most frequent first): transition clinics, patient/clinician forum, teaching, familiarisation with support groups and adult services, transition in usual clinical practice, seeing teenagers alone, curriculum. Conclusion: Trainees are unfamiliar with transition tools. Trainees are well aware of the need to assess the social impact of disease and promote independence, but less aware to explore disease understanding and risky activities. Trainees were not initially familiar with exploring support networks. The patient/clinician forum enabled trainees to consider different issues. We propose a clinic handout/questionnaire for teenagers in the waiting room which could be used to help physicians target the agenda considering all 8 identified themes. Attending transition clinics was the top suggestion to improve training. Other suggestions acknowledge the importance of facilitating transition within normal clinical practice and consulting teenagers alone. Teaching sessions should regularly provide a forum to learn from patients directly, include information about adult health services, patient support groups, and transition tools. Incorporating transition into curricula may encourage trainees to develop necessary skills.